The relationship between performance indicators and share prices of companies listed on sharia indices: a case study of S&P BSE 500 sharia index - Yasser Saleh Ali Almonifi; Vasant Keshavrao Bhosle (Fakultas Ekonomi dan Bisnis Islam UIN Salatiga, 2023)
This study aims to empirically examine the relationship between performance indicators and share prices of companies listed on SP BSE 500 sharia index. Data were collected through the index’s closing price and financial reports of the ten top companies listed on SP BSE 500 Sharia index. This study identifies the most important indicators that affect share prices in stock exchanges: ROA, ROE, EPS, and P/ER using Panel method. The study findings indicate that EPS, ROA and ROE have non-significant impact SP, while P/ER has a significant positive on SP. This study highlights the development of companies’ performance indicators and the enhancing of investment strategies for stakeholders and investors. This study is contributing to the analysis of the relationship between the companies’ performance indicators listed on sharia indices and their shares prices.